Exceeding the recruitment target in a primary care paediatric trial: an evaluation of the Choice of Moisturiser for Eczema Treatment (COMET) feasibility randomised controlled trial. Issue 1 (December 2016) - Powell, Kingsley; Wilson, Victoria; Redmond, Niamh; Gaunt, Daisy; Ridd, Matthew
Abstract Background Recruiting to target in randomised controlled trials of investigational medicinal products (CTIMPs) in primary care and paediatric populations is notoriously difficult. More evidence is needed for effective recruitment strategies in these settings. We report on the impact of different recruitment strategies used in the Choice of Moisturiser in Eczema Treatment (COMET) study – a feasibility trial comparing the effectiveness of four emollients for the treatment of childhood eczema – recruiting via general practitioner (GP) surgeries. Methods Initially, 16 GP practices invited potentially eligible children to take part in the trial by sending an invitation letter (self-referral pathway) or by consenting and randomising them into the study during a visit to the practice (in-consultation referral). Measures implemented during the study to maximise accrual included signing up six additional GP practices, increasing the upper age limit eligibility criterion from 3 to 5 years, and permitting healthcare professionals other than doctors to confirm participant eligibility. We used descriptive statistics and univariate linear regression models to explore associations with practice recruitment rates. Results A total of 197 participants were recruited, exceeding the target of 160. Of these, 107 children entered via self-referral and 90 by in-consultation pathways. Of the recruited population, 12.6 % were aged between 3 and 5 years (the raised upper age limit). The six additional practices contributed 37.4 % (40 of 107) of participants recruited by self-referral. Only almost one-third (18 of 56 [32.1 %]) of potential recruiting clinicians recruited one or more participants in-consultation, which was a more problematic pathway because of data verification issues. Three research nurses and a pharmacist from four practices recruited 48.9 % (44 of 90) of participants via this pathway. Univariate linear regression models showed no evidence of association between the number of children recruited via the self-referral pathway by practice and practice list size (p  = 0.092) or practice deprivation decile (p  = 0.270), but practice deprivation was associated with a higher number of children recruited in-consultation (p  = 0.020) by practice. Conclusions Self-referral and in-consultation recruitment yielded similar numbers, but the in-consultation pathway was more problematic. Future trials of this type should consider the condition, normal care pathway and number of potentially eligible children and be prepared to use multiple recruitment strategies to achieve recruitment targets. Trial registration ISRCTN21828118 . Registered on 1 May 2014. EudraCT2013-003001-26. Registered on 23 Dec 2013.